Stepping Up to Rethink the Future of Rehabilitation: IV STEP Considerations and Inspirations. (July 2017) - Kimberley, Teresa Jacobson; Novak, Iona; Boyd, Lara; Fowler, Eileen; Larsen, Deborah
Abstract : Background and Purpose: The IV STEP conference challenged presenters and participants to consider the state of science in rehabilitation, highlighting key area of progress since the previous STEP conference related to prediction, prevention, plasticity, and participation in rehabilitation. Key Points: Emerging from the thought-provoking discussions was recognition of the progress we have made as a profession and a call for future growth. In this summary article, we present a recap of the key points and call for action. We review the information presented and the field at large as it relates to the 4 Ps: prediction, prevention, plasticity, and participation. Recommendations for Practice: Given that personalized medicine is an increasingly important approach that was clearly woven throughout the IV STEP presentations, we took the liberty of adding a fifth "P, " Personalized, in our discussion of the future direction of the profession.